Plagiarism in undergraduate students: an approach from social representations - Strocchi Santos, María Verónica; Boysen Sánchez, Paulina; Barros Iverson, Verónica; Castillo Rabanal, Isidora Francisca (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This study seeks to account for the meaning that students assign to plagiarism, through the approach of social representations. The research design responded to a mixed study. This article focused on the analysis of qualitative data, carried out through the Grounded Theory procedure. The results allowed us to identify the different categories that make up the representation of plagiarism that students have. It should be noted that a negative assessment of this phenomenon predominates, which configures it as an obstacle to academic and professional development. However, students recognize that they do not always have the mechanisms to avoid it.